Domestic violence and violence against the girl-child and women: a comparative perspective between Islam and Nigerian custom - Raji, Barakat Adebisi; Ali Mohamed, Ashgar Ali; Ujah, Mariam O. (LexisNexis Malaysia Sdn. Bhd., 2017)
This article examines the violation of the rights of a girl child and that of women in Islam vis a vis what is prevalent in the Nigerian custom. The article provides a brief and authentic exposition of how custom, views women and the girl-child before the advent of Islam. One major objective of this article is to provide a fair evaluation of what Islam contributed towards the restoration of women's dignity rights before the birth of the Human Rights Instrument which have been adopted under the United Nations auspices for the protection of vulnerable groups, and women form part of the vulnerable groups and therefore need to be protected. The article finds that majority of the provisions set down for protection of these categories of people have not been fully explored as a result of societal and cultural influence on them. This article suggests that these provisions should be considered so as to whittle down the high rate of domestic violence in our society and disabuse the minds of people from causing grievous harm on girl-child and women. The article recommends that appropriate punishment should be meted out on person who violate the right to person of a girl-child and women.